1982
DOI: 10.1212/wnl.32.3.312
|View full text |Cite
|
Sign up to set email alerts
|

Low cerebrospinal fluid somatostatin in Parkinson disease

Abstract: In 39 parkinsonian patients, CSF somatostatin content was 88.0 +/- 4.1 pg per milliliter, which was about 40% less than in controls (147.3 +/- 5.1 pg per milliliter). Somatostatin values were unrelated to age, sex, body weight, total CSF protein, immunoglobulin, or cell count in either group. Parkinsonian values were not related to duration of disease, severity, specific signs, or treatment. In contrast to multiple sclerosis, in which CSF somatostatin is low only during relapses, the low somatostatin content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(33 citation statements)
references
References 0 publications
6
25
2
Order By: Relevance
“…Our finding of particularly low levels of SLI in the CSF of patient with parkinsonism is in agreement with earlier reports [9,11]. In one study, however, no signifi cant decrease of SLI was observed [3], and it was sug gested that SLI levels are reduced only in parkinsonian patients with dementia [4], In support of this, decreases of cerebral cortical SLI were observed only in PD pa tients with dementia but not in those without dementia [1], In this study no correlation between the presence or absence of dementia and the SLI concentration is noted, the small size of the group, however, precludes a gener alization.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our finding of particularly low levels of SLI in the CSF of patient with parkinsonism is in agreement with earlier reports [9,11]. In one study, however, no signifi cant decrease of SLI was observed [3], and it was sug gested that SLI levels are reduced only in parkinsonian patients with dementia [4], In support of this, decreases of cerebral cortical SLI were observed only in PD pa tients with dementia but not in those without dementia [1], In this study no correlation between the presence or absence of dementia and the SLI concentration is noted, the small size of the group, however, precludes a gener alization.…”
Section: Discussionsupporting
confidence: 94%
“…In patients with Parkinson's disease (PD) sub stantial decreases of somatostatin-like immunoreactivity (SLI) were observed in the CSF by several research groups [9,11] while no significant alteration was found by another [4], Marked decreases of CSF SLI were also reported in patients with Alzheimer's disease or senile dementia of Alzheimer type (SDAT) [8,20,27], In SDAT [10] as well as in PD [1,8] cerebral levels of the neuropeptide substance P (SP) were also decreased albeit to a lesser degree. Anatomic, biochemical and pharma cological studies have associated SP-ergic activity with dopaminergic neurons in the substantia nigra and the striatum [13,14,17] raising the issue of a possible involvement of SP in PD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in PD there is evidence of decrease of SLI in the cortex of demented patients and reduced SLI in the CSF (Dupont et al, 1982;Jolkkonen et al, 1986;Beal et al, 1986). Our demented PD patients showed slightly lower SLI than non-demented, but not significantly, possibly due to predominantly mild dementia.…”
Section: Discussionsupporting
confidence: 60%
“…In patients with PD, a reduced brain level of somatostatin (SOM) is frequently observed (3)(4)(5)(6)(7). In old Wistar rats, an inhibition of brain SOM receptors can produce catalepsy (8), an animal model of parkinsonian bradykinesia and rigidity.…”
Section: Introductionmentioning
confidence: 99%